Analysis of furfural in baby food Samples Using Solid-Phase Microextraction (SPME) and Gas Chromatography-Mass Spectrometry (GC-MS) / Ainur Syahidah Abdul Rahim - Abdul Rahim, Ainur Syahidah (2014)
The presence of furfural and other furanic compounds in many food types has been a concern lately. Furanic compounds such as furan and 5-hydroxymethylfuran had been detected to be harmful to human health. In this study the presence of furfural in baby food sample was analysed using solid phase microextraction (SPME) and gas chromatography mass spectrometry (GC-MS). The analysis used 5 types of baby food samples with different flavours which are apple purée, pear purée, pear and banana purée, carrot, parsnip and sweet potato purée, and peas and zucchini purée. The optimum conditions for SPME extraction were obtained. The optimum temperature was at 40°C while the optimum extraction time was at 30 minutes. The finding in this study showed that apple purée has the highest average furfural peak area value of 1.614xl09 compared to other samples. Pear and banana purée placed second with peak area of 1.115xl09 while pear purée was only slightly different from pear and banana purée with value of 1.108x109. Carrot, parsnip and sweet potato purée had the lowest average peak area with value of 0.018x109. Meanwhile peas and zucchini purée did not show any presence of furfural using the optimum conditions in this study.